2021
DOI: 10.1002/smll.202101620
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Catalysis by Single‐Atom Catalysts and Redox Mediator to Improve Lithium–Oxygen Batteries Performance

Abstract: to low round-trip efficiency as well as limited capacity. And cathode clogging arising from insulated, insoluble discharge products accumulation blocks the electron transfer and oxygen/Li + diffusion, resulting in a high overpotential for the electrochemical reactions, which will trigger parasitic reactions such as electrolyte oxidation. [5] As cathode corrosion aggravates, the batteries deliver poor cycle stability.Over the past few decades, numerous studies have intensively focused on cathodes and catalysts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 42 publications
(42 reference statements)
0
23
0
Order By: Relevance
“…Qiu et al [115] discovered the influence of the dimensionality of the graphene matrix on the formation of Fe SACs [Figure 5]. They revealed that single-shell hollow graphene spheres play a critical role in the preparation of single Fe atom catalysts.…”
Section: Sacs Supported On Single-shell Hollow Materialsmentioning
confidence: 99%
“…Qiu et al [115] discovered the influence of the dimensionality of the graphene matrix on the formation of Fe SACs [Figure 5]. They revealed that single-shell hollow graphene spheres play a critical role in the preparation of single Fe atom catalysts.…”
Section: Sacs Supported On Single-shell Hollow Materialsmentioning
confidence: 99%
“…Lithium peroxide is an insulator with a wide band gap, and its conductivity is poor, which leads to the inability of electrons to be transmitted timely, causing large polarization of the battery. In addition, Li 2 O 2 and the reaction intermediate LiO 2 both have high reactivity and are prone to react with the electrolyte to generate side reaction products, resulting in a decrease in the cycle life of the battery. It will be of great significance to develop non-Li 2 O 2 -based LOBs. Besides Li 2 O 2 , LiOH, LiO 2 , and even Li 2 O are also other reported reversible discharge products that are obtained by controlling catalysts and optimizing electrolyte systems. , Inspired by these works, we utilized the synergistic effect on the Co 3 O 4 (111) plane to enhance the electrochemical performance of LOBs in water-added electrolytes.…”
Section: Introductionmentioning
confidence: 99%
“…However, the development of LOBs is still hindered by several challenges, such as the limited cycle life, low discharge specific capacity, and poor rate performance, which are mainly due to the sluggish kinetics of the oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) at the oxygen cathodes [4–6] . Therein, Li + reacts with the oxygen to form the eventual Li 2 O 2 product during the discharging process, which decomposes to the Li + and oxygen in the subsequent charging process [7–11] . The major discharge product Li 2 O 2 , which is intrinsically insulating and insoluble in the electrolyte, is deposited on the cathode surface and further causes the degradation of the LOBs [12–15] .…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Therein, Li + reacts with the oxygen to form the eventual Li 2 O 2 product during the discharging process, which decomposes to the Li + and oxygen in the subsequent charging process. [7][8][9][10][11] The major discharge product Li 2 O 2 , which is intrinsically insulating and insoluble in the electrolyte, is deposited on the cathode surface and further causes the degradation of the LOBs. [12][13][14][15] To data, although some precious metals along with their oxides (Pt, Ru, IrO 2 , RuO 2 ) have shown excellent ORR and OER performance, they cannot be produced in a large scale due to the high cost and low reserve.…”
Section: Introductionmentioning
confidence: 99%